Kurgans with auxiliary cists, externally attached to the cromlech in Armenia - Melikyan, Varduhi; Tumanyan, Garegin (ARAMAZD: Armenian Journal of Near Eastern Studies, 2019)
Tomb complexes have been excavated at a number of necropoleis in Armenia, which, in addition to the main burial chamber, have also stone-made or ground cells, externally attached to the cromlech. These ritual ‘boxes’ usually contain accompanying property and in some cases the remains of sacrificed animals. Tombs with the mentioned structural peculiarities have been found in the necropoleis of Lori Berd, Karashamb, Kanagegh, Hnaberd, Horom, Shamiram, etc. These belong to the Middle Bronze Age – Early Iron Age cultures of Armenia. Although the auxiliary cists in almost all the complexes are smaller than the burial chamber, however, the vessels found in them usually outnumber (sometimes several times) the vessels found in the burial chamber. The construction of such auxiliary cists can be explained by certain funeral rites, which were usually performed after the burial, symbolising the memory of the deceased. As a rule, the orientation of the auxiliary cists differs significantly from that of the main burial chamber. This may be explained by the fact that the auxiliary cell or ‘cist’ was constructed slightly later than the main burial chamber. By measuring the angle of the longitudinal axis of the main tomb and the auxiliary cist, the degree of deviation can be seen of the point of the sun rising from the time of the tomb construction to the construction of auxiliary cist. Having determined the angle of these axes and knowing the maximum deviation angle of the sun’s rising from the eastern point (which appears in three months), one can find out how many days have passed since the auxiliary cist was built.